The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/atmos13060923
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Distributions and Transport over Southern Morocco from Ground-Based and Satellite Observations (2004–2020)

Abstract: The present study investigates the optical properties of aerosols on daily and seasonal scales with the use of the aerosol optical depth (AOD) and Angström exponent (AE) data retrieved from AErosol RObotic NETwork (AERONET) and collected at four stations in Southern Morocco—Saada (31.63° N; 8.16° W), Ouarzazate (30.93° N; 6.91° W), Oukaïmeden (31.21° N; 7.86° W) and Ras-El-Aïn (31.67° N; 7.60° W). An evaluation of the aerosol volumetric size distribution (AVSD) is also obtained for Saada and Ouarzazate. An AOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…However, MERRA-2 seems to be in better agreement with the ground-based AERONET observations. These results are consistent with the finding reported by Millet et al [52] in their comparative study for the same region. To determine the type of aerosols during the event, the daily VSD derived from AERONET observations at Saada between 1 and 5 of August were superimposed on Figure 5b.…”
Section: Aeronet Ground-based Datasupporting
confidence: 94%
“…However, MERRA-2 seems to be in better agreement with the ground-based AERONET observations. These results are consistent with the finding reported by Millet et al [52] in their comparative study for the same region. To determine the type of aerosols during the event, the daily VSD derived from AERONET observations at Saada between 1 and 5 of August were superimposed on Figure 5b.…”
Section: Aeronet Ground-based Datasupporting
confidence: 94%
“…We clustered the trajectories using TrajStat, an algorithm developed by Wang et al [54] as a GIS-based program to view, query, and group the trajectories. This program had already been used in the study of Millet et al [55] in the identification and analysis of the observed seasonal aerosol variations over Southern Morocco. The number of clusters can be visually determined by inspecting the total spatial variation (TSV) curve before a net increase in TSV (see Figure A2, in Appendix A).…”
Section: Hysplit Back-trajectoriesmentioning
confidence: 99%
“…These datasets have provided data on the characteristics of cloud, various aerosol, and other atmospheric products since 1979. The aerosol products of MERRA-2 are obtained by the assimilation of data from AErosol RObotic NETwork (AERONET) stations, Moderate Resolution Imaging Spectroradiometer MODIS), and many other station data [29]. MERRA-2 datasets include global observable parameters and aerosol diagnostics with different times (1 month, 3 h, and 1 h) at spatial resolutions (0.5 • × 0.625 • ).…”
Section: Modern-era Retrospective Analysis For Research and Applicati...mentioning
confidence: 99%